Perceived Organizational Support and Performance: A Meta-Analysis Study - Handayani, Arri (ANIMA Indonesian Psychological Journal, 2013)
This study conducted a meta-analysis in order to see the link between perceived organisational support (POS) and work performance. Organizational Support Theory and Social Exchange Theory (Blau, 1964) was used as a framework for discussing correlation between POS and work performance. After meta-analysis was conducted to 20 primary study with as many as 6,645 subjects, the result showed that on the average correlation coefficient was .219 (r^ = .219), with the corrected SD being .1048. The differences of various correlations could be caused by, among others, sampling error of 23.75% and 1.42% for the error in measuring either dependent or independent variables. Therefore, hypothesis stating that there is positive correlation between POS and work performance could be accepted. Studi ini melakukan meta-analisis dengan tujuan melihat keterkaitan antara persepsi terhadap dukungan organisasi dan kinerja.. Teori dukungan organisasi dan teori pertukaran sosial digunakan untuk membahas hubungan antara persepsi terhadap dukungan organisasi dan kinerja. Setelah dilakukan meta-analisis terhadap 20 studi primer dengan 6,645 subjek, diperoleh rata-rata koefisien korelasi sebesar .219 (r^= .219), dengan SD yang dikoreksi sebesar .1048. Perbedaan variasi korelasi dapat disebabkan antara lain kesalahan pengambilan sampel sebesar 23.75% dan kesalahan pengukuran variabel bebas maupun tergantung sebesar 1.42%. Dengan demikian, hipotesis yang menyatakan ada hubungan positif antara persepsi terhadap dukungan organisasi dan kinerja dapat diterima.